2020
DOI: 10.3390/biom10101446
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 Expression in Synovial Sarcoma May Support Neural Origin

Abstract: Synovial sarcoma (SS) is a malignant mesenchymal soft tissue neoplasm. Despite its name, the cells of origin are not synovial cells, but rather neural, myogenic, or multipotent mesenchymal stem cells have been proposed as possible cells originators. Unlike other sarcomas, an unusual presentation of long-term pain at the tumor site has been documented, but the exact mechanisms have not been fully clarified yet. The transient receptor potential ankyrin 1 (TRPA1) is a nonselective cation channel mainly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…For genes whose average expression was higher (“up” in Table 1 ) in each tumor subtype, the lowest and average log-normalized expression values were 3.06 (HOXA9) and 5.84 for fibrosarcomas, 1.6 (XKR7) and 5.33 for peripheral nerve sheath tumors, and 3.33 (FBP1) and 6.83 for perivascular wall tumors. For comparison, the average log normalized expression value for the transcription factor SNAIL (SNAI1), which play a key role regulating the behavior of some sarcoma cell types [ 45 , 46 ] was 3.50 for all samples in this study, while that of keratin 13 (KRT13), which is expressed in epithelial cell types [ 47 ] but is not expected to be significantly expressed in soft tissue sarcomas, was -1.47. For genes expressed at lower levels in each tumor subtype (labeled “down” in Table 1 ), the average log normalized expression value of genes in the other two tumor subtypes for the 25 down-regulated genes was 5.27 for fibrosarcomas, 5.22 for peripheral nerve sheath tumors and 6.5 for perivascular wall tumors.…”
Section: Resultsmentioning
confidence: 96%
“…For genes whose average expression was higher (“up” in Table 1 ) in each tumor subtype, the lowest and average log-normalized expression values were 3.06 (HOXA9) and 5.84 for fibrosarcomas, 1.6 (XKR7) and 5.33 for peripheral nerve sheath tumors, and 3.33 (FBP1) and 6.83 for perivascular wall tumors. For comparison, the average log normalized expression value for the transcription factor SNAIL (SNAI1), which play a key role regulating the behavior of some sarcoma cell types [ 45 , 46 ] was 3.50 for all samples in this study, while that of keratin 13 (KRT13), which is expressed in epithelial cell types [ 47 ] but is not expected to be significantly expressed in soft tissue sarcomas, was -1.47. For genes expressed at lower levels in each tumor subtype (labeled “down” in Table 1 ), the average log normalized expression value of genes in the other two tumor subtypes for the 25 down-regulated genes was 5.27 for fibrosarcomas, 5.22 for peripheral nerve sheath tumors and 6.5 for perivascular wall tumors.…”
Section: Resultsmentioning
confidence: 96%
“…The exact cell of origin for synovial sarcoma remains to be determined. However, the two leading hypotheses are a mesenchymal stem cell found in the periosteum [ 7 ] or stem cells associated with neural crest cells [ 8 ]. Cytogenetic analysis, FISH, or RT-PCR can be used to detect the translocation or the protein product of the fusion gene, thus aiding in the diagnosis of synovial sarcoma [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local recurrence occurs after an average of 3.6 years and metastasis after an average of 5.7 years, and the lung is the most common site of metastasis (Krieg et al, 2011); therefore, the prognosis is poor. The origin of SS is uncertain, and studies have shown that it is derived from mesenchymal stem cells (De Logu et al, 2020). However, recent studies have suggested that neural, myogenic, or multipotent mesenchymal stem cells are considered to be the likely cellular origin (De Logu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of SS is uncertain, and studies have shown that it is derived from mesenchymal stem cells (De Logu et al, 2020). However, recent studies have suggested that neural, myogenic, or multipotent mesenchymal stem cells are considered to be the likely cellular origin (De Logu et al, 2020). It has been shown that the gene expression profile of SS is closely related to malignant peripheral nerve sheath tumors and that neural tissue-associated genes are expressed in SS tissues (Ishibe et al, 2008).…”
Section: Discussionmentioning
confidence: 99%